Molecular genetic characterization of the L-lactate dehydrogenase gene (ldhL) of Lactobacillus helveticus and biochemical characterization of the enzyme. - Savijoki, K (1997)
The Lactobacillus helveticus L-(+)-lactate dehydrogenase (L-LDH) gene (ldhL) was isolated from a lambda library. The nucleotide sequence of the ldhL gene was determined and shown to have the capacity to encode a protein of 323 amino acids (35.3 kDa). The deduced sequence of the 35-kDa protein revealed a relatively high degree of identity with other lactobacillar L-LDHs. The highest identity (80.2%) was observed with the Lactobacillus casei L-LDH. The sizes and 5' end analyses of ldhL transcripts showed that the ldhL gene is a monocistronic transcriptional unit. The expression of ldhL, studied as a function of growth, revealed a high expression level at the logarithmic phase of growth. The ldhL gene is preceded by two putative -10 regions, but no corresponding -35 regions could be identified. By primer extension analysis, the ldhL transcripts were confirmed to be derived from the -10 region closest to the initiation codon. However, upstream of these regions additional putative -10/-35 regions could be found. The L-LDH was overexpressed in Escherichia coli and purified to homogeneity by two chromatographic steps. The purified L-LDH was shown to be a nonaliosteric enzyme, and amino acid residues involved in allosteric regulation were not conserved in L. helveticus L-LDH. However, a slight enhancement of enzyme activity was observed in the presence of fructose 1,6-diphosphate, particularly at neutral pH. A detailed enzymatic characterization of L-LDH was performed. The optimal reaction velocity was at pH 5.0, where the kinetic parameters K(m), and Kcat for pyruvate were 0.25 mM and 643 S-1, respectively.